Absolutely Continuous Functions of Several Variables - MALY, J (Journal of mathematical analysis and applications, 1999)
A class of “absolutely continuous functions” ofnvariables is introduced. The absolute continuity implies continuity, weak differentiability with gradient inLn, differentiability almost everywhere, area, coarea and degree formulae. This gives a unified approach to some previously known conditions for the mentioned results based on monotonicity, finite dilatation or higher integrability of the gradient.